Effect of Varying Nutrient Density of Diets on Productive Performance in Dahlem Red Layers - Prakash, Bhukya; Rao, S.V. Rama; Raju, M.V.L.N.; Verma, S. K.; Panda, A. K. (Indian Journal of Animal Nutrition, 2019)
The study was conducted to optimize the nutrient requirement for Dahlem Red (DR) birds. Five diets were formulated Â i.e., one basal diet (BD) with optimum (100%) nutrients, two diets with lower (97.5 % and 95%) and two diets with higher (102.5% and 105%) nutrients to the BD. A total of 240 number of DR layers of 23 weeks were selected and divided into 5 groups, each having 8 replicates and each replicate had 5 birds. The experiment was continued up to 70 weeks. Feed intake was higher (P